Firms' employment dynamics and the state of the labor market - Karolina Stadin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
According to search and matching theory, a greater availability of unemployed workers should make it easier for a firm to fill a vacancy but more vacancies at other firms should make recruitment more difficult. But what can we say about the expected magnitudes of these effects on firms' employment dynamics? In this paper, I simulate a theoretical model featuring search frictions in the labor market, imperfect competition in the product market and quadratic adjustment costs. The simulations show quite small employment effects of typical shocks to the number of vacancies in the local labor market and very small effects of typical shocks to the number of unemployed. The employment effects are smaller in recessions than in booms. Estimation of an employment equation using panel data for Swedish firms suggests that neither the number of unemployed nor the number of vacancies in the local labor market are important for firms' employment dynamics. Thus, the empirical results are in line with the predictions from the theoretical simulations.
Keywords: E24; J23; J63; J64; 330; employment dynamics; search and matching frictions